1987
DOI: 10.1007/bf02910430
|View full text |Cite
|
Sign up to set email alerts
|

Yeast cells may use AUC or AAG as initiation codon for protein synthesis

Abstract: A yeast expression plasmid without an ATG codon for initiation of mouse a-amylase protein synthesis directs the synthesis and secretion of active enzyme indistinguishable from both native mouse a-amylase and amylase synthesized from plasmids with normal AT(3 initiation codons. The initiation of amylase synthesis directed by this plasmid is at either an AUC or an AAG codon. In either case the amino acid sequence of the hydrophobic core and peptidase cleaving region of the signal peptide are normal, and the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several recent reports demonstrate the use of a number of non-AUG codons for translation initiation in eukaryotes, especially those that differ from AUG only by a single base substitution (Olsen, 1987;Kozak, 1989a and references therein;Peabody, 1989). Interestingly, ACG and AUA codons can be used as weak start codons for the P gene of duck hepatitis B virus (Schlicht et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports demonstrate the use of a number of non-AUG codons for translation initiation in eukaryotes, especially those that differ from AUG only by a single base substitution (Olsen, 1987;Kozak, 1989a and references therein;Peabody, 1989). Interestingly, ACG and AUA codons can be used as weak start codons for the P gene of duck hepatitis B virus (Schlicht et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This was first observed in bacteria (Looman and van Knippenberg, 1986;Munson etal., 1984;Reddy etal., 1985;Wulff eta/., 1984;Yakota et a/., 1980); with eukaryotic systems, in-witm studies have shown that some triplets are capable of initiating translation at astonishingly high levels (Mehdi et a/., 1990;Peabody, 1987), but these observations depend to a great degree on the precise translation conditions employed and are therefore of dubious physiological significance (Kozak, 1989). Initiation at non-AUG triplets has also been observed in yeast, where it remains very inefficient and of doubtful physiological significance (Clements eta/., 1988;Oonahue and Cigan, 1988;Olsen, 1987;Zitomer eta/., 1984). More recently, such initiation has been observed in mammalian cells (Peabody, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…An AUC codon within the open reading frame can be used as an alternative initiation codon (Chalut and Egly, 1995). In eukaryotes, a subset of mRNAs also initiate at an AUC codon (Ivanov et al, 2011; Olsen, 1987). Whereas non-AUG initiation has been shown to be remarkably prevalent (Ingolia et al, 2009; Ivanov et al, 2011), the structural basis of recognition of non-AUG initiation codons by the initiator tRNA in the P site is unknown.…”
Section: Introductionmentioning
confidence: 99%